Emerging Adults' Conceptions of Purpose and the Good Life: A Classification and Comparison. Issue 6 (September 2018) - Glanzer, Perry L.; Hill, Jonathan P.; Robinson, Jessica A.
To understand the purpose acquisition of young emerging adults (18-23), scholars claim we need to learn the types of purposes to which they are committing and how they conceptualize purpose differently from other related concepts such as future goals and the good life. To address these issues, we examined interviews with 229 young emerging adults about their life purpose, future goals, and conceptions of the good life. Although the interviewees' purposes and future goals fit within shared categories of achievement, relationships, religion, and moral concerns, important differences also emerged. While one fourth of the sample lacked purpose, no one lacked a vision for the good life or future goals. Moreover, their future vision of the good life focused more on individualistic concerns such as happiness, material acquisitions and personal experiences with family being the only communal interest.